Chromium-containing wastewater adsorbing material and preparation method thereof

By in situ polymerizing polyphenylenediamine nanoparticles on cellulose acetate fibers, the problem of low adsorption efficiency of polyaromatic amine adsorption materials is solved, and efficient Cr(VI) adsorption and material retrievalability are achieved.

CN119507217AActive Publication Date: 2025-02-25HENAN ACADEMY OF SCIENCES +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411696087.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing polyaromatic amine-containing chromium-containing wastewater adsorption materials have the problem of low adsorption efficiency, especially because the nanoparticles are too small and difficult to recover and prone to agglomeration, resulting in low adsorption efficiency of Cr(VI).

Method used

By reacting the phenylenediamine monomer with cellulose acetate fibers in Schiff base and oxidative polymerization under the action of an oxidant, the in-situ polymerization of polyphenylenediamine nanoparticles on cellulose acetate fibers is achieved, thereby improving the load uniformity of the nanoparticles and avoiding agglomeration.

Benefits of technology

The adsorption amount to Cr(VI) is increased to 434.78 mg/g, and due to the stable combination of nanoparticles and fibers, the material is easy to recover, reducing the cost of use and the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507217A_ABST
    Figure CN119507217A_ABST
Patent Text Reader

Abstract

The invention relates to a chromium-containing wastewater adsorption material and a preparation method thereof, and belongs to the technical field of heavy metal ion adsorption materials. The preparation method of the chromium-containing wastewater adsorbing material comprises the following steps: firstly carrying out Schiff base reaction on cellulose acetate fiber and phenylenediamine, and then carrying out oxidative polymerization reaction under the action of an oxidizing agent to obtain the chromium-containing wastewater adsorbing material. The preparation method of the chromium-containing wastewater adsorbing material is simple and easy to operate, and the particle size and distribution of the polyphenylenediamine nanoparticles can be adjusted by adjusting the proportion of the cellulose acetate fiber and the phenylenediamine monomer and the reaction time of the cellulose acetate fiber and the phenylenediamine monomer. The chromium-containing wastewater adsorbing material prepared by the method has the fiber form of cellulose acetate fiber, and the Cr (VI) adsorbing capacity can reach 434.78 mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a chromium-containing wastewater adsorption material and a preparation method thereof, belonging to the technical field of heavy metal ion adsorption materials. Background Art

[0002] Chromium-containing wastewater is the main pollutant discharged by industries such as electroplating, leather making and metallurgy. With the acceleration of industrialization in recent years, the discharge volume has been increasing. Among them, Cr(VI) poses a great threat to the ecological environment and human health because of its strong physiological toxicity and can be enriched along the food chain. At present, the main treatment methods for Cr(VI) wastewater include adsorption, chemical precipitation, electrochemical reduction, flocculation and microbial degradation. Among them, adsorption has become one of the main methods preferred in practical applications due to its advantages such as simple operation, easy separation and recovery, low cost and no secondary pollution. The efficiency of adsorbing Cr(VI) mainly depends on the performance of the adsorbent. Therefore, the development of chromium-containing wastewater adsorption materials with large adsorption capacity, high efficiency, environmental protection and wide sources has become the main task and research hotspot for treating chromium-containing wastewater.

[0003] Polyaromatic amines have gradually attracted attention due to their advantages such as high functional group density, stable structure and high Cr(VI) adsorption performance. Among them, polyphenylenediamine shows unique high adsorption capacity and selectivity in the adsorption of Cr(VI). In addition, the morphological characteristics of the polymer can be changed by changing the reaction conditions or adding specific active reagents. Most polyphenylenediamines are nanoparticles (including spherical nanoparticles, nanobelts, nanorods, nanofibers, etc.), which are conducive to full contact with pollutants and increase the mass transfer rate. However, polyphenylenediamine nanoparticles are difficult to recycle due to their small size, which will cause secondary pollution and increase the cost of use. In addition, polyphenylenediamine nanoparticles are easy to agglomerate, resulting in low adsorption efficiency for Cr(VI). Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a chromium-containing wastewater adsorbent material, which can solve the problem of low adsorption efficiency of the currently prepared polyaromatic amine chromium-containing wastewater adsorbent material.

[0005] Another object of the present invention is to provide a chromium-containing wastewater adsorption material, which can solve the problem of low adsorption efficiency of current polyaromatic amine-based chromium-containing wastewater adsorption materials.

[0006] In order to achieve the above purpose, the technical solution adopted by the preparation method of the chromium-containing wastewater adsorbent of the present invention is:

[0007] A method for preparing a chromium-containing wastewater adsorbent material comprises the following steps: first subjecting cellulose acetate fiber and phenylenediamine to a Schiff base reaction, and then subjecting them to an oxidative polymerization reaction under the action of an oxidant to obtain the chromium-containing wastewater adsorbent material.

[0008] The preparation method of the chromium-containing wastewater adsorbent of the present invention comprises the following steps: grafting a phenylenediamine monomer onto cellulose acetate fiber through a Schiff base reaction to obtain a composite, and then utilizing an oxidative polymerization reaction between an amino group on the composite and an amino group in the phenylenediamine monomer to realize in-situ polymerization of polyphenylenediamine nanoparticles on cellulose acetate fiber, thereby improving the uniformity of the loading of polyphenylenediamine nanoparticles on cellulose acetate fiber and avoiding agglomeration of polyphenylenediamine nanoparticles. The preparation method of the chromium-containing wastewater adsorbent of the present invention is simple and easy to operate, and the particle size and distribution of polyphenylenediamine nanoparticles can be adjusted by adjusting the ratio of cellulose acetate fiber and phenylenediamine monomer and the reaction time of cellulose acetate fiber and phenylenediamine monomer. The chromium-containing wastewater adsorbent prepared by the present invention has the fiber morphology of cellulose acetate fiber, and the adsorption amount of Cr(VI) can reach 434.78 mg / g.

[0009] Preferably, the mass ratio of the phenylenediamine to the cellulose acetate fiber is 1:(1-50).

[0010] Preferably, the mass ratio of the phenylenediamine to the cellulose acetate fiber is 1:(10-20).

[0011] Preferably, the Schiff base reaction time is 0.5 to 3 hours.

[0012] Preferably, the phenylenediamine is meta-phenylenediamine.

[0013] Preferably, the molar ratio of the phenylenediamine to the oxidant is 1:(1-3).

[0014] Preferably, the oxidant is potassium persulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide or ferric chloride.

[0015] Preferably, the oxidant is added in the form of a solution, and during the process of adding the oxidant and the oxidative polymerization reaction, the pH of the reaction system is controlled to be 4-7.

[0016] Preferably, the cellulose acetate fiber is prepared by a method comprising the following steps: ultrasonically dispersing the cigarette filter fiber and water, separating the solid from the liquid, washing, soaking the washed solid in an alkali solution to remove impurities, then washing the soaked solid, and freeze-drying to obtain the cellulose acetate fiber; the cigarette filter fiber is a fiber bundle with a length of 0.5 to 1 cm and a diameter of 1 to 5 μm.

[0017] The technical solution adopted by the chromium-containing wastewater adsorbent material of the present invention is:

[0018] A chromium-containing wastewater adsorption material prepared by the method for preparing the chromium-containing wastewater adsorption material as described above.

[0019] The chromium-containing wastewater adsorption material of the present invention comprises cellulose acetate fiber and polyphenylenediamine nanoparticles chemically bonded to the cellulose acetate fiber, has a fiber form, can avoid agglomeration of the polyphenylenediamine nanoparticles when used, has an adsorption capacity of up to 434.78 mg / g for Cr(VI), and is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The scanning electron microscope images of the chromium-containing wastewater adsorbent materials prepared in Examples 1-9 of the present invention;

[0021] Figure 2 This is a transmission electron micrograph of the chromium-containing wastewater adsorbent material prepared in Example 8 of the present invention;

[0022] Figure 3 The infrared spectra of the chromium-containing wastewater adsorbent material prepared by cellulose acetate, poly-m-phenylenediamine and Examples 1-6 in the present invention;

[0023] Figure 4 The Raman spectra of the chromium-containing wastewater adsorbent materials prepared in Examples 1-5 of the present invention;

[0024] Figure 5 This is a Raman spectrum scan of the chromium-containing wastewater adsorbent material prepared in Examples 1-9 of the present invention;

[0025] Figure 6 The chromium-containing wastewater adsorbent prepared in Examples 1-9 of the present invention has different concentrations of K 2 Cr 2 O 7 Schematic diagram of the saturated adsorption capacity of Cr(VI) in solution;

[0026] Figure 7 The chromium-containing wastewater adsorbent prepared in Examples 1-9 of the present invention has a K 2 Cr 2 O 7 Schematic diagram of the experimental results of adsorption kinetics of Cr(VI) in solution;

[0027] Figure 8 The K of the chromium-containing wastewater adsorbent prepared in Example 8 of the present invention at different pH values 2 Cr 2 O 7 Schematic diagram of the saturated adsorption capacity of Cr(VI) in solution;

[0028] Fig. 9 This is a schematic diagram of the recovery and regeneration test of the chromium-containing wastewater adsorbent material prepared in Example 8 of the present invention. DETAILED DESCRIPTION

[0029] The preparation method of the chromium-containing wastewater adsorbent material of the present invention is a pioneering invention. The preparation method of the chromium-containing wastewater adsorbent material of the present invention is based on the problem that the current polyphenylenediamine nanoparticles are easy to agglomerate, resulting in low adsorption efficiency of Cr(VI). The polyphenylenediamine nanoparticles are grafted onto cellulose acetate molecular chains to avoid agglomeration of the polyphenylenediamine nanoparticles and improve the dispersion uniformity of the polyphenylenediamine nanoparticles, thereby improving the adsorption efficiency of the material for Cr(VI).

[0030] The polyphenylenediamine nanoparticles in the present invention are obtained by polymerizing phenylenediamine monomers. The structure and reaction mechanism of the polymer are as follows:

[0031]

[0032] The preparation method of the chromium-containing wastewater adsorbent material of the present invention comprises the following steps: subjecting the amino groups in the phenylenediamine monomer and the carbonyl groups on the cellulose acetate fiber to Schiff base reaction to obtain a composite, and then subjecting the amino groups on the composite and the amino groups in the phenylenediamine monomer to oxidative polymerization reaction under the action of an oxidant to obtain the chromium-containing wastewater adsorbent material.

[0033] In the present invention, the cellulose acetate fiber can be obtained from commercial sources or prepared from cigarette filter fibers.

[0034] In some preferred embodiments, the cellulose acetate fiber is prepared by a method comprising the following steps: ultrasonically dispersing cigarette filter fibers and water, separating solids from liquids, washing, and then soaking the washed solids in alkali solution, and then washing the soaked solids, freeze-drying, to obtain cellulose acetate fibers; the soaking temperature is 50 to 90° C., and the time is 6 to 12 hours; the alkali solution is a sodium hydroxide solution with a mass fraction of 35 to 45%.

[0035] In some preferred embodiments, the cigarette filter fiber has a length of 0.5 to 1 cm and a diameter of 1 to 5 μm.

[0036] The chromium-containing wastewater adsorbent prepared by the present invention can deposit the fibers into a uniform membrane material by simple suction filtration, and can obtain membrane materials with different thicknesses, porosities and mechanical properties by controlling the mass of the composite fibers per unit area. Preferably, the mass of the composite fibers per unit area is 0.1 g / cm 2 .

[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0038] The specific embodiments of the chromium-containing wastewater adsorbent material and the preparation method thereof of the present invention are as follows:

[0039] Example 1

[0040] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0041] (1) Preparation of cellulose acetate fiber

[0042] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours to remove impurities such as grease, and then washed three times with deionized water and ethanol respectively, and then solvent exchanged with tert-butyl alcohol (solvent exchange with tert-butyl alcohol can maintain the stable structure of the fiber), and then freeze-dried at -78°C for 24 hours to obtain cellulose acetate fiber (Cellulose acetate, CA).

[0043] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0044] 0.1 g of cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution, and immediately (here immediately means that the Schiff base reaction time between cellulose acetate fiber and m-phenylenediamine is approximately 0) 25 mL of 8.44 mg / mL (NH 4 ) 2 S 2 O 8 The solution (the molar ratio of ammonium persulfate to m-phenylenediamine is 1:1) was added dropwise, and the pH value of the material in the three-necked flask was adjusted to 4-7 with 2 mol / L NaOH solution while the ammonium persulfate solution was added dropwise. After the addition of the ammonium persulfate solution was completed, the material in the three-necked flask was heated to 30°C and the reaction was continued at a constant temperature and stirred for 5 hours. During the heating and stirring reaction, 2 mol / L NaOH solution was added dropwise to adjust the pH value of the material in the three-necked flask to 4-7. After the reaction was completed, the material in the three-necked flask was stirred with a 120 mesh The solid was separated by mesh filtration, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0045] Example 2

[0046] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0047] (1) Preparation of cellulose acetate fiber

[0048] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0049] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0050] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The mixture was stirred at 600 rpm at 50 °C for 0.5 h in an atmosphere. After the reaction was completed, 25 mL of 8.44 mg / mL (NH 4 ) 2 S 2 O 8 The solution (the molar ratio of ammonium persulfate to m-phenylenediamine is 1:1) was added dropwise, and the pH value of the material in the three-necked flask was adjusted to 4-7 with 2 mol / L NaOH solution while the ammonium persulfate solution was added dropwise. After the addition of the ammonium persulfate solution was completed, the material in the three-necked flask was heated to 30°C and the reaction was continued at a constant temperature and stirred for 5 hours. During the heating and stirring reaction, 2 mol / L NaOH solution was added dropwise to adjust the pH value of the material in the three-necked flask to 4-7. After the reaction was completed, the material in the three-necked flask was stirred with a 120 mesh The solid was separated by mesh filtration, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0051] Example 3

[0052] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0053] (1) Preparation of cellulose acetate fiber

[0054] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0055] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0056] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The mixture was stirred at 600 rpm at 50 °C for 1 h in an atmosphere. After the reaction was completed, 25 mL of 8.44 mg / mL (NH 4 ) 2 S 2 O 8 The solution (the molar ratio of ammonium persulfate to m-phenylenediamine is 1:1) was added dropwise, and the pH value of the material in the three-necked flask was adjusted to 4-7 with 2 mol / L NaOH solution while the ammonium persulfate solution was added dropwise. After the addition of the ammonium persulfate solution was completed, the material in the three-necked flask was heated to 30°C and the reaction was continued at a constant temperature and stirred for 5 hours. During the heating and stirring reaction, 2 mol / L NaOH solution was added dropwise to adjust the pH value of the material in the three-necked flask to 4-7. After the reaction was completed, the material in the three-necked flask was stirred with a 120 mesh The solid was separated by mesh filtration, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0057] Example 4

[0058] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0059] (1) Preparation of cellulose acetate fiber

[0060] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0061] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0062] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The mixture was stirred at 600 rpm at 50 °C for 2 h in an atmosphere. After the reaction was completed, 25 mL of 8.44 mg / mL (NH 4 ) 2 S 2 O 8 The solution (the molar ratio of ammonium persulfate to m-phenylenediamine is 1:1) was added dropwise, and the pH value of the material in the three-necked flask was adjusted to 4-7 with 2 mol / L NaOH solution while the ammonium persulfate solution was added dropwise. After the addition of the ammonium persulfate solution was completed, the material in the three-necked flask was heated to 30°C and the reaction was continued at a constant temperature and stirred for 5 hours. During the heating and stirring reaction, 2 mol / L NaOH solution was added dropwise to adjust the pH value of the material in the three-necked flask to 4-7. After the reaction was completed, the material in the three-necked flask was stirred with a 120 mesh The solid was separated by mesh filtration, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0063] The preparation method of the chromium-containing wastewater adsorbent of Examples 5-9 specifically comprises the following steps:

[0064] (1) Preparation of cellulose acetate fiber

[0065] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0066] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0067] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of m-phenylenediamine solution and stirred at N 2 The mixture was stirred at 600 rpm at 50 °C for 3 h in an atmosphere. After the reaction was completed, 25 mL of 8.44 mg / mL (NH 4 ) 2 S 2 O 8 The solution (the molar ratio of ammonium persulfate to m-phenylenediamine is 1:1) was added dropwise, and the pH value of the material in the three-necked flask was adjusted to 4-7 with 2 mol / L NaOH solution while the ammonium persulfate solution was added dropwise. After the addition of the ammonium persulfate solution was completed, the material in the three-necked flask was heated to 30°C and the reaction was continued at a constant temperature and stirred for 5 hours. During the heating and stirring reaction, 2 mol / L NaOH solution was added dropwise to adjust the pH value of the material in the three-necked flask to 4-7. After the reaction was completed, the material in the three-necked flask was stirred with a 120 mesh The solid was separated by mesh filtration, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0068] In the preparation methods of chromium-containing wastewater adsorbent materials of Examples 5-9, the mass fractions of the m-phenylenediamine solution are 1 mg / mL, 5 mg / mL, 10 mg / mL, 20 mg / mL and 50 mg / mL, respectively.

[0069] In other embodiments, the molar ratio of ammonium persulfate to m-phenylenediamine is 1:3, or ammonium persulfate is replaced by potassium persulfate, sodium persulfate, hydrogen peroxide or ferric chloride.

[0070] Example 10

[0071] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0072] (1) Preparation of cellulose acetate fiber

[0073] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0074] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0075] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The reaction was stirred at 600 rpm at 50 °C for 3 h in an atmosphere. The pH value of the reaction system was measured with a pH meter during the stirring reaction. After the reaction was completed, 25 mL of 10 mg / mL K was added dropwise to the three-necked flask at a rate of 0.5 mL / s. 2 S 2 O 8 The solution (the molar ratio of potassium persulfate to m-phenylenediamine is 1:1) is prepared, and the pH value of the material in the three-necked flask is adjusted to 4-7 with a 2 mol / L NaOH solution while dropping the potassium persulfate solution. After the dropping is completed, the material in the three-necked flask is heated to 30°C, and the reaction is continued at a constant temperature and stirred for 5 hours. After the reaction is completed, the material in the three-necked flask is filtered and separated with a 120-mesh sieve, and the filtered solid is repeatedly ultrasonically washed with deionized water until the filtrate is colorless, and then washed three times with ammonia water (the mass fraction of ammonia water is 25% to 28%) and anhydrous ethanol respectively (ammonia water is used to neutralize the sulfuric acid produced by the reaction, and ethanol is used to remove oligomers), and then the washed solid is rinsed with tert-butyl alcohol to replace the solvent adsorbed by the solid, and finally the rinsed solid is freeze-dried at -26°C for 12 hours to obtain cellulose acetate @ poly-m-phenylenediamine composite fiber, which is the chromium-containing wastewater adsorption material.

[0076] Embodiment 11

[0077] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0078] (1) Preparation of cellulose acetate fiber

[0079] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0080] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0081] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The reaction was stirred at 600 rpm at 50 °C for 3 h in an atmosphere. During the stirring reaction, the pH value of the reaction system was measured with a pH meter. After the reaction was completed, a certain amount of H with a concentration of about 0.004 mol / L was added to the three-necked flask at a rate of 0.5 mL / s. 2 O 2 Solution (H 2 O 2 The solution was prepared before the experiment, and the concentration was determined by potassium permanganate titration. The volume was controlled to ensure that the molar ratio of the solution to m-phenylenediamine was 1:1. Then, 25 mL of 4×10 -4 mol / LFeSO 4 The solution and 10mL of 1.0mol / L sulfuric acid solution were all added dropwise, and the material in the three-necked flask was heated to 30°C, and the reaction was continued at a constant temperature and stirred for 5h. After the reaction was completed, the material in the three-necked flask was filtered and separated with a 120-mesh sieve, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12h to obtain cellulose acetate @ poly(m-phenylenediamine) composite fiber, which is the chromium-containing wastewater adsorption material.

[0082] Example 12

[0083] The preparation method of the chromium-containing wastewater adsorbent of the present embodiment specifically comprises the following steps:

[0084] (1) Preparation of cellulose acetate fiber

[0085] The tobacco shreds and outer wrapping paper of the discarded cigarette butts were removed, and the filter fiber part was retained. The filter fiber was cut into fiber bundles with a length of 0.5-1 cm and a diameter of 1-5 μm, and mechanically separated using a ball mill. 1 g of filter fiber was dispersed in 200 mL of deionized water, and ultrasonically dispersed for 3 hours using an ultrasonic crusher. After washing, the dispersed fibers were further dispersed in a 40% NaOH aqueous solution at a constant temperature of 50°C for 12 hours, and then washed three times with deionized water and ethanol respectively, and after solvent exchange with tert-butyl alcohol, they were freeze-dried at -78°C for 24 hours to obtain cellulose acetate fibers (Celluloseacetate, CA).

[0086] (2) Preparation of adsorbent materials for chromium-containing wastewater

[0087] 0.1 g of the cellulose acetate fiber prepared in step (1) was dispersed in a three-necked flask containing 100 mL of 1 mg / mL m-phenylenediamine solution and stirred at N 2 The reaction was stirred at 600 rpm at 50 °C for 3 h in an atmosphere. During the stirring reaction, the pH value of the reaction system was measured with a pH meter. After the reaction was completed, a certain amount of FeCl with a concentration of about 0.004 mol / L was added to the three-necked flask at a rate of 0.5 mL / s. 3 Solution (FeCl 3 The solution was prepared before the experiment, and the concentration was determined by o-phenanthroline-spectrophotometer. The volume was controlled to ensure that the amount ratio with m-phenylenediamine was 1:1). After the addition was completed, the material in the three-necked flask was heated to 30°C, and the reaction was continued at a constant temperature and stirred for 5 hours. After the reaction was completed, the material in the three-necked flask was filtered and separated with a 120-mesh sieve, and the filtered solid was repeatedly ultrasonically washed with deionized water until the filtrate was colorless, and then washed three times with ammonia water (the mass fraction of ammonia water was 25% to 28%) and anhydrous ethanol (ammonia water was used to neutralize the sulfuric acid produced by the reaction, and ethanol was used to remove oligomers), and then the washed solid was rinsed with tert-butanol to replace the solvent adsorbed by the solid. Finally, the rinsed solid was freeze-dried at -26°C for 12 hours to obtain cellulose acetate@polym-phenylenediamine composite fiber, which is the chromium-containing wastewater adsorption material.

[0088] Experimental Example 1

[0089] This experiment is used to analyze the mass percentage of poly(m-phenylenediamine) nanoparticles in chromium-containing wastewater adsorption materials. The calculation formula for the mass percentage of poly(m-phenylenediamine) nanoparticles in chromium-containing wastewater adsorption materials is as follows:

[0090]

[0091] Among them, w 产物 is the mass of chromium-containing wastewater adsorption material, in g, w CA is the mass of cellulose acetate fiber, in g.

[0092] The calculation results show that the mass percentages of poly(m-phenylenediamine) nanoparticles in the chromium-containing wastewater adsorbent prepared in Examples 1-9 are 1.96%, 11.11%, 17.23%, 21.26%, 21.88%, 59.18%, 73.16%, 77.19% and 74.25%, respectively. This result shows that as the adsorption reaction time of m-phenylenediamine monomer increases, the amount of poly(m-phenylenediamine) nanoparticles attached to the surface of cellulose acetate fiber increases. Examples 5 to 9 illustrate that as the mass ratio of cellulose acetate fiber to m-phenylenediamine monomer decreases, the amount of poly(m-phenylenediamine) nanoparticles attached to the surface of cellulose acetate fiber increases, but as the m-phenylenediamine monomer is excessively added, after the mass ratio exceeds 1:20, the mass percentage of poly(m-phenylenediamine) nanoparticles in the adsorbent material tends to be stable. This shows that the loading amount of m-phenylenediamine in the in-situ polymerization reaction depends on the total amount of m-phenylenediamine monomer adsorbed by the fiber. When the fiber adsorbs m-phenylenediamine monomer to saturation, continuing to increase the concentration of m-phenylenediamine monomer cannot increase the loading amount.

[0093] Experimental Example 2

[0094] This experimental example analyzes the appearance of the chromium-containing wastewater adsorbent prepared in Examples 1-9. The chromium-containing wastewater adsorbent prepared in Examples 1-9 was analyzed using a scanning electron microscope (SEM). Figure 1 As shown; Figure 1 a-1i are scanning electron microscope images of the chromium-containing wastewater adsorbent materials prepared in Examples 1-9, respectively. In addition, the appearance of the chromium-containing wastewater adsorbent material prepared in Example 8 was analyzed and characterized using a transmission electron microscope (TEM). Figure 2 As shown; Figure 2 a is a picture of poly(m-phenylenediamine) nanoparticles attached to the fiber surface. Figure 2 b is a picture of poly(m-phenylenediamine) nanoparticles grown by polymerization inside the fiber bundle. Figure 2 c and 2d are the interface images of cellulose acetate fibers and poly(m-phenylenediamine) nanoparticles at different resolutions.

[0095] Depend on Figure 1It can be seen that after in-situ polymerization of polyaniline on cellulose acetate fibers, poly(m-phenylenediamine) nanoparticles with diameters ranging from tens to hundreds of nanometers were observed on the cellulose acetate fibers ( Figure 1 a~1i). With the increase of the adsorption reaction time of m-phenylenediamine monomer, the poly-m-phenylenediamine nanoparticles are more evenly attached to the surface of cellulose acetate fiber. When the mass ratio of cellulose acetate fiber to m-phenylenediamine monomer is reduced from 1:1 to 1:5, the diameter of the poly-m-phenylenediamine nanoparticles increases significantly (about 3 times). In addition, with the increase of the ratio of cellulose acetate fiber to m-phenylenediamine monomer, the diameter of the poly-m-phenylenediamine nanoparticles tends to be uniform. However, when the m-phenylenediamine monomer is added in excess, the poly-m-phenylenediamine nanoparticles agglomerate and accumulate ( Figure 1 i). Therefore, by changing the reaction time of the m-phenylenediamine monomer and the cellulose acetate fiber and the mass ratio of the m-phenylenediamine monomer to the cellulose acetate fiber, the diameter and quantity of the poly-m-phenylenediamine nanoparticles loaded on the cellulose acetate fiber can be controlled. A large number of carbonyl groups on the cellulose acetate can react with the m-phenylenediamine monomer to form a Schiff base structure, making the combination of the poly-m-phenylenediamine and the cellulose acetate fiber more stable and thus preventing the nanoparticles from falling off.

[0096] Depend on Figure 2 It can be seen that poly(m-phenylenediamine) nanospheres are formed on cellulose acetate fibers by in situ polymerization and can be incorporated into cellulose acetate fibers in two ways, e.g. Figure 2 a and 2b. Poly(m-phenylenediamine) nanoparticles grow on the surface of cellulose acetate fibers ( Figure 2 a) and embedded in cellulose acetate fibers ( Figure 2 b) This phenomenon may be due to the -NH 2 - reacts with the C=O of cellulose acetate to form a Schiff base structure, which then enters the cellulose acetate fiber bundle and induces the formation of poly(m-phenylenediamine) nanoparticles wrapped by the fiber band. This type of structure can effectively prevent the nanoparticles from falling off the cellulose acetate fiber. Microscopic image ( Figure 2 c and 2d) confirmed the uneven boundary fusion or bonding of poly(m-phenylenediamine) nanoparticles and cellulose acetate fibers, further proving the stable bonding between the two.

[0097] Experimental Example 3

[0098] This experimental example characterizes the structure of the chromium-containing wastewater adsorbent prepared in Examples 1-9. Infrared analysis and Raman spectroscopy were performed on cellulose acetate, poly(m-phenylenediamine) and the chromium-containing wastewater adsorbent prepared in Examples 1-6. The results are as follows: Figure 3 , Figure 4 and Figure 5 shown. Figure 3In the figure, 1 represents cellulose acetate, 2 represents poly(m-phenylenediamine), 3 represents the chromium-containing wastewater adsorbent material prepared in Example 1, 4 represents the chromium-containing wastewater adsorbent material prepared in Example 2, 5 represents the chromium-containing wastewater adsorbent material prepared in Example 3, 6 represents the chromium-containing wastewater adsorbent material prepared in Example 4, 7 represents the chromium-containing wastewater adsorbent material prepared in Example 5, and 8 represents the chromium-containing wastewater adsorbent material prepared in Example 6. Figure 4 In the figure, 1 represents the chromium-containing wastewater adsorbent material prepared in Example 1, 2 represents the chromium-containing wastewater adsorbent material prepared in Example 2, 3 represents the chromium-containing wastewater adsorbent material prepared in Example 3, 4 represents the chromium-containing wastewater adsorbent material prepared in Example 4, and 5 represents the chromium-containing wastewater adsorbent material prepared in Example 5. Figure 5 a-5i are Raman spectra of the chromium-containing wastewater adsorbent materials prepared in Examples 1-9, respectively.

[0099] Depend on Figure 3 It can be seen that cellulose acetate fiber exhibits multiple infrared absorption peaks, namely -OH stretching vibration (3200~3500cm -1 ),-CH 2 -Stretching vibration (2893cm -1 ) and COC asymmetric stretching vibration (1159cm -1 For poly(m-phenylenediamine), the main absorption peaks are: located at 3500-3000cm -1 -NH-, located at 1625cm -1 The quinone imine, located at 1500cm -1 The aniline structure and the -1 CN. Characteristic peaks similar to those of poly(m-phenylenediamine) were observed in the cellulose acetate@poly(m-phenylenediamine) composite fiber sample, indicating that poly(m-phenylenediamine) was composited with cellulose acetate fiber. With the increase of adsorption reaction time, the intensities of -NH-, quinoneimine and aniline increased relatively due to the formation of more poly(m-phenylenediamine). In addition, when the mass ratio of cellulose acetate to m-phenylenediamine monomers decreased from 1:1 to 1:5, the relative intensity of the characteristic peaks of poly(m-phenylenediamine) in the product increased. It is worth noting that the CN absorption peak of poly(m-phenylenediamine) after composite increased from 1257cm -1 Red shifted to 1281 cm -1 , and the strength increases. This is due to the -NH 2 The addition reaction with C=O on the cellulose acetate molecular chain formed a Schiff base structure, confirming the strong interaction between cellulose acetate fibers and poly(m-phenylenediamine) nanoparticles.

[0100] Depend on Figure 4 It can be seen that for cellulose acetate, the -1The peak is the COC asymmetric stretching vibration of the glycoside ring and polysaccharide. -1 The strong peak is the stretching vibration of symmetrical CH. For poly(m-phenylenediamine), the peak at 1573 cm -1 and 1352cm -1 The two strong peaks belong to the characteristic absorption bands of aniline and quinoneimine, respectively. In order to study the relative distribution of poly(m-phenylenediamine) nanoparticles in cellulose acetate fiber matrix, and considering the absorption band of 1573 cm -1 The peak intensity is high, so the Raman scan is performed based on this peak position (such as Figure 5 The red color indicates the relatively high density of poly(m-phenylenediamine) nanoparticles. The results show that only when the m-phenylenediamine monomer is fully reacted with cellulose acetate can the poly(m-phenylenediamine) nanoparticles be evenly distributed on the fiber.

[0101] Experimental Example 4

[0102] In this experimental example, the chromium-containing wastewater adsorbent prepared in Examples 1-9 was used to treat chromium-containing wastewater. The chromium-containing wastewater adsorbent prepared in Examples 1-9 was named CA@PmPD (1:1) 0 、CA@PmPD(1:1) 0.5 、CA@PmPD(1:1) 1 、CA@PmPD(1:1) 2 、CA@PmPD(1:1) 3 、CA@PmPD(1:5) 3 、CA@PmPD(1:10) 3 、CA@PmPD(1:20) 3 、CA@PmPD(1:50) 3 .

[0103] ① Constant temperature adsorption experiment

[0104] 25 mg of chromium-containing wastewater adsorbent material was added to 50 mL of K solution with an initial concentration of 100-500 mg / L and pH = 2. 2 Cr 2 O 7 The solution was shaken at 150 rpm at 30°C for 4 h (at this time, the chromium-containing wastewater adsorption material reached saturation in the adsorption of chromium ions), and then the solution was filtered with a filter membrane with a pore size of 0.45 μm, and the filtrate was collected. The concentration of Cr(VI) in the filtrate was determined by diphenylcarbazide-spectrophotometry at a wavelength of 540 nm.

[0105] After the experiment, the adsorption amount was calculated according to the following formula:

[0106]

[0107] Among them, C 0 is the initial concentration of the solution, m is the mass of the adsorbent added, V is the volume of the solution, q e is the saturated adsorption capacity of the adsorbent, C e is the concentration of the solution when adsorption reaches saturation.

[0108] Effects of different chromium-containing wastewater adsorption materials on different concentrations of K 2 Cr 2 O 7 The saturated adsorption amount of Cr(VI) in the solution is as follows: Figure 6 And as shown in Table 1. Among them, Figure 6 a is the chromium-containing wastewater adsorbent prepared in Examples 1-5 for different concentrations of K 2 Cr 2 O 7 Schematic diagram of the adsorption results of chromium ions in solution concentration. Figure 6 b is the chromium-containing wastewater adsorbent prepared in Examples 5-9 for different concentrations of K 2 Cr 2 O 7 Schematic diagram of the adsorption results of chromium ions in solution concentration. The Langmuir adsorption isotherm model is used to fit the experimental data. Langmuir is a classic monolayer adsorption isotherm model, and its mathematical expression is as follows:

[0109]

[0110] Among them, C e is the equilibrium solution concentration (mg / L), q e is the adsorption amount of the adsorbent at equilibrium (mg / g), q m is the theoretical maximum adsorption capacity of the adsorbent (mg / g), and b is the thermodynamic constant (L / mg).

[0111] Table 1 Isothermal adsorption data of Cr(VI) on different chromium-containing wastewater adsorption materials

[0112]

[0113] From Table 1 and Figure 6 It can be seen that the adsorption process of Cr(VI) by the chromium-containing wastewater adsorption material prepared in Examples 1-9 conforms to the Langmuir model, indicating that the adsorption mechanism is single-layer adsorption, and the maximum saturated adsorption capacity of Cr(VI) by the chromium-containing wastewater adsorption material prepared in Examples 1-9 can reach 434.78 mg / g.

[0114] ② Adsorption kinetics experiment

[0115] 25 mg of chromium-containing wastewater adsorbent material was added to 50 mL of K solution with an initial concentration of 500 mg / L and pH = 2. 2 Cr2 O 7 The solution was shaken at 150 rpm at 30°C for 0.5 to 4 h, and then the solution was filtered through a filter membrane with a pore size of 0.45 μm, and the filtrate was collected. The concentration of Cr(VI) in the filtrate was determined by diphenylcarbazide-spectrophotometry at a wavelength of 540 nm.

[0116] After the experiment, the adsorption amount was calculated according to the following formula: Chromium-containing wastewater adsorption material prepared in Examples 1-9

[0117]

[0118] Among them, q t is the adsorption amount after t time, C 0 is the initial concentration of the solution, C t is the concentration of the solution after adsorption for t time, m is the mass of the added adsorbent, and V is the volume of the solution.

[0119] The mathematical expression of the pseudo-first-order kinetic model is as follows:

[0120]

[0121] Among them, q e is the saturated adsorption capacity, q t is the adsorption amount of the adsorbent in time t (mg / g), k 1 is the pseudo-first-order kinetic constant.

[0122] The mathematical expression of the pseudo-second-order kinetic model is:

[0123]

[0124] Among them, q e is the saturated adsorption capacity, q t is the adsorption amount of the adsorbent in time t (mg / g), k 2 is the pseudo-second-order kinetic constant.

[0125] The experimental data were fitted according to the pseudo-first-order kinetic model and the pseudo-second-order kinetic model to obtain the values ​​of each parameter in the model. The effects of different chromium-containing wastewater adsorption materials on K 2 Cr 2 O 7 The adsorption kinetic data of Cr(VI) in solution are shown in Table 2 and Figure 7 shown.

[0126] Table 2 Effect of different chromium-containing wastewater adsorption materials on K 2 Cr 2 O 7 Adsorption kinetics of Cr(VI) in solution

[0127]

[0128] From Table 2 and Figure 7 It can be seen that the adsorption material is more suitable for the description of the pseudo-second-order kinetic model. It can be seen that in the adsorption process of Cr(VI) by the polymeric Schiff base and its reduction product, chemical adsorption is the rate-controlling step. The chromium-containing wastewater adsorption material prepared in Example 1-9 can reach 67% of the saturated adsorption capacity within 0.5h, and has a high adsorption rate.

[0129] ③ Effect of solution pH on saturated adsorption capacity

[0130] 25 mg of the chromium-containing wastewater adsorbent prepared in Example 8 was added to 7 bottles of 50 mL of K with an initial concentration of 500 mg / L. 2 Cr 2 O 7 The solution was adjusted to pH = 0, 1, 2, 3, 4, 5, 6, respectively, and oscillated at 150 rpm for 4 h at 30 ° C. After the oscillation, the solution was filtered and the filtrate was collected. The concentration of Cr (VI) in the filtrate was determined by diphenylcarbazide-spectrophotometry at a wavelength of 540 nm. The experimental results are shown in Figure 8 As shown. Figure 8 It can be seen that the chromium-containing wastewater adsorption material prepared in Example 8 has good acid resistance and stability, and the saturated adsorption capacity is the largest when pH=2.

[0131] Experimental Example 5

[0132] This experimental example is an adsorption material recovery and regeneration test. The experimental steps are as follows: 100 mg of the chromium-containing wastewater adsorption material prepared in Example 8 is added to 200 mL of K with an initial concentration of 500 mg / L. 2 Cr 2 O 7 The solution was adjusted to pH = 2, and the mixture was shaken at 150 rpm for 4 h at 30 °C. After the mixture was finished, the adsorbent material was recovered by vacuum filtration using a 50 mm diameter filter membrane. The adsorbent material can form a membrane (such as Fig. 9 Left side), add to water (such as Fig. 9 After that, it can be dispersed in water again by stirring (as shown in the middle picture) Fig. 9As shown in the figure on the right). The adsorbent material was ultrasonically dispersed in a 1 mol / L NaOH solution and ultrasonic desorption was continued for 2 h. After the regeneration of the adsorbent material was completed, the adsorbent material was washed with deionized water, and then the washed adsorbent material was rinsed with tert-butyl alcohol to replace the solvent adsorbed by the solid. Finally, the regenerated adsorbent material was freeze-dried at -26 ° C for 12 h and used for the second adsorption, the method was the same as the constant temperature adsorption experiment in Experimental Example 4. After five cycles, the adsorption capacity of Cr(VI) remained at 98%, 89%, 82%, 78% and 73% of the initial adsorption capacity, respectively, indicating that the synthesized adsorbent material has good regeneration performance.

Claims

1. A method for preparing a chromium-containing wastewater adsorbent material, characterized in that: The method comprises the following steps: firstly subjecting cellulose acetate fiber and phenylenediamine to a Schiff base reaction, and then subjecting them to an oxidative polymerization reaction under the action of an oxidant to obtain a chromium-containing wastewater adsorption material.

2. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1, characterized in that: The mass ratio of the phenylenediamine to the cellulose acetate fiber is 1:(1-50).

3. The method for preparing the chromium-containing wastewater adsorbent material according to claim 2, characterized in that: The mass ratio of the phenylenediamine to the cellulose acetate fiber is 1:(10-20).

4. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1, characterized in that: The reaction time of the Schiff base is 0.5 to 3 hours.

5. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1, characterized in that: The phenylenediamine is meta-phenylenediamine.

6. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1, characterized in that: The molar ratio of the phenylenediamine to the oxidant is 1:(1-3).

7. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1 or 6, characterized in that: The oxidant is potassium persulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide or ferric chloride.

8. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1 or 6, characterized in that: The oxidant is added in the form of a solution, and during the process of adding the oxidant and the oxidative polymerization reaction, the pH of the reaction system is controlled to be 4-7.

9. The method for preparing the chromium-containing wastewater adsorbent material according to claim 1, characterized in that: The cellulose acetate fiber is prepared by a method comprising the following steps: ultrasonically dispersing cigarette filter fiber and water, separating solid from liquid, washing, soaking the washed solid in alkali solution to remove impurities, then washing the soaked solid, and freeze-drying to obtain the cellulose acetate fiber; the cigarette filter fiber is a fiber bundle with a length of 0.5 to 1 cm and a diameter of 1 to 5 μm.

10. A chromium-containing wastewater adsorbent material prepared by the method for preparing a chromium-containing wastewater adsorbent material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Application method of polymetaphenylene diamine adsorbent to treatment of sexivalent-Cr-containing acidic wastewater

    CN102432084A

  • Preparation method of nanofiber membrane formaldehyde test paper

    CN102978912A

  • Cellulose acetate-based composite aerogel as well as preparation method and application thereof

    CN114934385A

  • Textile gas-liquid-solid contactors and biocatalytic materials and methods comprising same

    EP4326929A1

  • Process for the treatment of cellulose acetate fiber

    US4612013A